Cervical Length as a Predictor of Preterm Delivery in an Unselected Cohort of Women with Twin Pregnancies - Brock, Clifton O.; Moroz, Leslie A.; Gyamfi-Bannerman, Cynthia (American Journal of Perinatology, 2019)
Objective To determine the risk of spontaneous preterm delivery (SPTD) associated with transvaginal cervical length (TVCL) in an unselected cohort.Study Design This is a retrospective study of serial TVCLs in unselected twin gestations. Receiver operator curves for SPTD were constructed from TVCLs at 18, 20, 22, and 24 weeks. Prediction thresholds were determined using a false discovery rate of 10%. The risk of SPTD was compared with previously published, prospective data from a meta-analysis.Results A total of 1,228 women were included. SPTD occurred prior to 35 weeks in 232 (18.9%), 126 (10.3%), and 24 (2.0%) women prior to 35, 32, and 28 weeks. TVCL was most predictive at 22 weeks (area under the curve = 0.67). TVCL thresholds for predicting SPTD prior to 35, 32, and 28 weeks were 3.1, 3.0, and 2.9 cm. Compared with a previous meta-analysis, the risk of SPTD < 34, 32, and 28 weeks was lower (positive likelihood ratio 9.0 vs. 5.4, 10.1 vs. 5.9, and 9.6 vs. 4.3).Conclusion TVCL is modestly predictive of SPTD in twin gestations. Compared with previous prospective studies, this cohort has lower risk of SPTD at similar TVCLs.
Keywords: transvaginal cervical length; twin gestations; preterm birth; prenatal; ultrasound